Learning styles-based approach for enhanced e-resource integration in ecological education - Tetiana M. Derkach; Tetiana V. Starova; Alexander V. Krajnikov (CTE Workshop Proceedings)
This paper explores optimizing electronic resources in teaching ecological chemistry aligned with students' educational preferences to develop sustainability competencies. We employ an approach to select e-resources based on individual learning preferences, teaching styles, and discipline content. The R. Felder and B. Soloman model was used to study learning preferences of students at Kryvyi Rih State Pedagogical University majoring in chemistry and informatics and students at Kyiv National University of Technologies and Design majoring in industrial pharmacy. Most students in both groups demonstrate visual, sensing, active, and sequential learning preferences. Based on these profiles, didactic materials for the ``Ecological chemistry of the lithosphere'' topic were developed. We propose expanding ecological chemistry curriculum by incorporating environmental pollution of medicinal plants, which aligns with the prevailing sensitive learning style while strengthening ecological competencies needed for sustainable development. This approach connects to recent frameworks like GreenComp by fostering sustainability values, embracing complexity, and envisioning sustainable futures. Through balanced development of different cognitive functions, students become more adaptable to technological advancement, open to diverse information sources, and capable of processing information without resistance - key competencies for transformation toward sustainability.